The Hero's Life-Choice - Studies on Heracles at the Crossroads, the Judgement of Paris, and Their Reception : 'Verbalising the Visual and Visualising the Verbal' - Davies, Malcolm, (Metaforms ;, 2023)
Two allegorical ancient Greek stories about a young hero's career- defining choice are shown in this book to have later been appropriated to radically differing effects. E.g. a male's choice between female personifications can morph into a female's choice between the same, or between various male personifications. Never before have so many instances of this process from art, literature, music, even landscape gardening, been culled. Illustrations, mainly colour, many brought into this context for the first time, are conveniently incorporated into the text, thus mimetically mirroring a central theme of the book, the process of 'visualising the verbal, verbalising the visual.'